Semantics of Estimation in Pronouns - Газарова, Диана (Bulletin of Yerevan University H: Russian Philology, 2021)
The article touches upon the Russian pronouns from the standpoint of the category of estimation. Almost all categories of pronouns are capable of expressing and softening or strengthening the estimation. This article examines the demonstrative and indefinite pronouns from the standpoint of the estimation they express. Demonstrative pronouns, the main function of which is an indication, are capable of expressing a negative estimation, strengthening the speaker's attitude to the statement. Indefinite pronouns are able to express not only and not so much an indefinite meaning, but rather a relative, optional indefiniteness, as well as a dismissive attitude of the speaker towards the phenomenon and participants in the situation. The speaker's attitude is especially vividly manifested in combinations of demonstrative and indefinite pronouns with proper names. In these cases we are dealing with the expression of relative indefiniteness, since here indefiniteness fades into the background: the speaker's attitude becomes more important (usually a negative, dismissive attitude). Pronouns not only strengthen the estimation: in many cases statements without pronouns become less emotionally and expressively convincing.
Keywords: indefinite pronouns; demonstrative pronouns; category of estimation; relative indefiniteness; proper names